Essential fish habitats of demersal fish in the western Arabian Gulf. (December 2021) - Lin, Yu-Jia; Roa-Ureta, Ruben H.; Pulikkoden, Abdu Rahiman Kambrath; Premlal, Panickan; Nazeer, Zahid; Qurban, Mohammad A.; Rabaoui, Lotfi
Abstract: Information about habitats occupied by aquatic organisms while completing critical stages of their lives, called essential fish habitats, is crucial for their sustainability. In this work, we determine essential fish habitats (nursery and spawning grounds) of several fish species inhabiting Saudi territorial waters in the western Arabian Gulf using data from multiple surveys (2013–2016), geostatistics, and indicator species analysis. We built geostatistical maps of spatial distributions of juvenile and mature fish and examined the strength of association of each species to its observed nursery and spawning areas. Fish nursery areas were generally located in nearshore locations while spawning areas were located in offshore waters. The patterns of nursery and spawning grounds were highly varied among species, supporting a hypothesis of habitat-species heterogeneity: different species use different locations as nursery and spawning grounds. This information can be used as a roadmap for future evidence-based spatial planning and ecosystem-based management. Highlights: We identified the nursery grounds for 56 fish and shell fish taxa and the spawning ground for 6 fish taxa. The patterns of using nursery and spawning grounds were highly varied among species. This information can be used as a roadmap for future evidence-based spatial planning and ecosystem-based management.